The role of Smyrnium cordifolium Boiss extract and curzerene on withdrawal syndrome in mice - Pari, Nazari; Parichehreh, Yaghmaei; Alireza, Rangin; Naser, Abbasi (Cellular and Molecular Biology, 2019)
Morphine is the most effective medication to relieve pain, antinociception and withdrawal syndrome, but clinical application of these compounds is greatly affected by the occurrence of addiction. The aim of this research was the influence of SE and curzerene (Cur) on withdrawal syndrome signs in mice contrasted with clonidine. Extraction of the S. cordifolium extract (SE) was done by the Soxhlet method. Addiction was produced using the subcutaneous injections of morphine for 7 days. To estimate the influences of SE and Cur, the 64 male mice were separated into eight of 8. Sets 1, 2 and 3 were treated SE (100,200,300 mg/kg). Sets 4, 5 and 6 were treated Cur (0.03, 0.06, 0.12mg/kg). The findings showed that curzerene was the most important effective component S. cordifolium extract. Curzerene and SE reduced the mean of weight loss, diarrhea, and wet dog shakes in morphine-dependent mice in comparison with clonidine. All doses of Curzerene and SE extract reduced the locomotor activity and body weight loss when compared to the control group in morphine-dependent mice but not to clonidine compared. The SE (100mg/kg) and Cur (0.03mg/kg) are reduced signs of withdrawal syndrome equally to clonidine. SE (200 mg/kg) and Cur (0.06 mg/kg), are reduced of the body weight loss significantly in relation to clonidine (P<0.05). SE (200 mg/kg) and Cur (0.06 mg/kg), are reduced of diarrhea significantly in relation to clonidine (P<0.01). This was while SE (300mg/kg) and cur (0.12mg/kg) had deadly effect. Curzerene and SE are able to decrease the signs of withdrawal syndrome, which might have a human therapeutic capacity. Curzerene may be one of the terpenoids responsible for the effect of the S. cordifolium extract. Nevertheless, more investigations are needed to determine the exact mechanism of the effect of SE and curzerene.